The Impact Of Giving Gadgets By Parents on Children's Social Behavior At Aisyiyah Maccini Kindergarten In Central Makassar City - As Fatahillah, Nurul Auliah; Alwi, M. Ahkam (Polteknik Ilmu Pemasyarakatan, 2025)
This research is based on the impact of giving gadgets on the social behavior of early childhood. This is proven by the existence of students at the Aisyiyah Maccini Tengah Kindergarten in Makassar City who are often given gadgets by their parents. The aim of this research is to determine the impact of giving parents gadgets on the social behavior of young children. This research uses a qualitative descriptive approach with a case study method. This research was carried out at the Aisyiyah Maccini Tengah Kindergarten, Makassar City, with the objects of this research being 2 children and their parents as well as the teacher/class teacher. Data collection for this research is observation, interviews, documentation and recording. Validity test uses source triangulation techniques. Data analysis techniques use data reduction, data presentation and conclusions or verification. The results of this research show that there are negative and positive impacts of gadgets on the social behavior of young children. Such as applications that are often opened by children, namely YouTube, TikTok and games. This use has a positive impact on gaining extensive knowledge, facilitating communication and training children's creativity. Apart from that, it has negative impacts, including eyes becoming tired easily, reduced sleep and study hours and emotional disturbances in children. Children's social behavior still shows good, respect for others, mutual help, good manners, but children are less sensitive and caring towards the people around them.